2018
DOI: 10.1186/s12917-018-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of mammaglobin-B in canine mammary tumors

Abstract: BackgroundMammaglobin, a member of secretoglobin family has been recognized as a breast cancer associated protein. Though the exact function of the protein is not fully known, its expression has been reported to be upregulated in human breast cancer.We focused on studying the expression of mammaglobin-B gene and protein in canine mammary tumor (CMT) tissue. Expression of mammaglobin-B mRNA and protein were assessed by quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Hence, need of the hour is to add a few more specific CMT biomarkers to the existing panel for accurate diagnosis and prognosis of the disease. In the last few years, our laboratory has put considerable efforts in search of markers for non-invasive diagnosis and prognosis of CMT (Sunil Kumar et al 2013Pandey et al 2015Pandey et al , 2017Pandey et al , 2018Kaur et al 2016). Advanced research in cancer biology has shown the importance of Hsps as biomarkers of carcinogenesis and their potential in prognosis of some human cancer types (Salda and Romanucci 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, need of the hour is to add a few more specific CMT biomarkers to the existing panel for accurate diagnosis and prognosis of the disease. In the last few years, our laboratory has put considerable efforts in search of markers for non-invasive diagnosis and prognosis of CMT (Sunil Kumar et al 2013Pandey et al 2015Pandey et al , 2017Pandey et al , 2018Kaur et al 2016). Advanced research in cancer biology has shown the importance of Hsps as biomarkers of carcinogenesis and their potential in prognosis of some human cancer types (Salda and Romanucci 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical (IHC) score of the NK-1 receptor was obtained by multiplying the intensity and positivity scores (range 1-12). IHC scores below 6 were considered to reflect low expression, whereas those over 6 were considered to reflect high expression of the NK-1 receptor at the tissue level (Pandey et al, 2018).…”
Section: Semi-quantitative Scoring Of Positive Cellsmentioning
confidence: 99%
“…However, differentially expressed biomarkers can also be used for more speci c diagnosis. Hence, identi cation and characterization of CMT speci c/associated biomarkers is greatly encouraged for speci c diagnosis of this malady [4].…”
Section: Introductionmentioning
confidence: 99%